Circular RNA in Lung Cancer Research: Biogenesis, Functions, and Roles - Zhang, Congcong (Int J Biol Sci, 2020)
Lung cancer is one of the most common and deadly malignancies worldwide, in spite of advances in targeted therapy in recent years. An effective strategy for lung cancer prevention remains a major problem. Advances in next-generation sequencing have helped in understanding the RNA and identifying novel circular RNAs (circRNAs) that may have a broad impact on the early diagnosis and treatment of lung cancer. The circRNAs, exhibiting spatiotemporal-specific expression, are stable and conserved and present diverse biological functions in the normal and diseased states, including cancer. In this review, we summarize the recent advances in elucidating the functional role of circRNAs in lung cancer pathogenesis and discuss their potential mechanisms.